Ecclesiology and theosis in the gospel of John - Byers, Andrew J. (Society for New Testament Studies Monograph Series, 2017)
John's Gospel directs attention to the vision of community. Andrew Byers argues that ecclesiology is as central a Johannine concern as Christology